2015
DOI: 10.7763/ijiet.2015.v5.477
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of Marital Satisfaction of Batangueño Couples: Components of Love and the Other External Factors in Marriage

Abstract: Abstract-This study dealt with the correlation between the levels of Sternberg's components of love (intimacy, passion and commitment) and the level of marital satisfaction of selected married couples in Batangas. Moreover, the levels of components of love and levels of marital satisfaction based on the varying profile of the respondents are compared. A survey method using questionnaires (Triangular Theory of Love Scale (TTLS) and Couples Satisfaction Index (CSI-32)) translated in Filipino language were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
7
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 4 publications
2
7
0
1
Order By: Relevance
“…Several studies have examined marital satisfaction, each study focused on relevant variables, Some studies emphasized on the importance of love in the occurrence of marital satisfaction such as study Carandang & Guda (2015), Other studies have tested the effect of communication in marital relationships such as study of Abbasi & Afsharinia (2015), The effect of age on marital satisfaction was also discussed in Dabone (2014), One of the variables studied in relation to marital satisfaction was the Rebello et al study (2014), which found an impact on love, partnership, and jealousy in determining the level of marital satisfaction, while the study by Javanmard & Garegozlo (2014) showed the role of some personal factors in marital satisfaction, related variables were Villa & Prette (2013) in Brazil, which dealt with social skills on marital satisfaction, The study of Yadalijamaloye et al (2013) focused on the study of the effect of selfassessment on marital satisfaction, this study sample was large and included only women, Bloch et al (2013) focused on the role of emotional exchange among couples and its impact on the level of marital satisfaction. The study of Zainah et al (2012) also examined the variables of the duration of marriage and income and its impact on levels of marital satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined marital satisfaction, each study focused on relevant variables, Some studies emphasized on the importance of love in the occurrence of marital satisfaction such as study Carandang & Guda (2015), Other studies have tested the effect of communication in marital relationships such as study of Abbasi & Afsharinia (2015), The effect of age on marital satisfaction was also discussed in Dabone (2014), One of the variables studied in relation to marital satisfaction was the Rebello et al study (2014), which found an impact on love, partnership, and jealousy in determining the level of marital satisfaction, while the study by Javanmard & Garegozlo (2014) showed the role of some personal factors in marital satisfaction, related variables were Villa & Prette (2013) in Brazil, which dealt with social skills on marital satisfaction, The study of Yadalijamaloye et al (2013) focused on the study of the effect of selfassessment on marital satisfaction, this study sample was large and included only women, Bloch et al (2013) focused on the role of emotional exchange among couples and its impact on the level of marital satisfaction. The study of Zainah et al (2012) also examined the variables of the duration of marriage and income and its impact on levels of marital satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to the Filipino culture, Carandang and Guda [7] said that the Philippines is a country for friendliness and closeness among individuals, which can be important in maintaining relationships. As one of the most treasured values in the Filipino culture, Filipinos have close family ties.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that there was a relationship between love and marital satisfaction of husband and wives (Carandang & Guda, 2015;Hoesni, Subhi, Alavi, & Wan Azreena, 2013;Tung, 2007;Muchtar, 2004). However, the studies differ in the component of love that has the highest correlation with marital satisfaction.…”
mentioning
confidence: 97%
“…Commitment can be divided into short-term and longterm commitment where short term commitment relates to a decision to love a person and long-term commitment relates to the acts of maintaining love (Sternberg, 1997). If love in particular the three components of love are at the same high level, it is most likely that high marital satisfaction will be attained and maintained (Carandang & Guda, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation